Edukasi kemandirian hand hygiene menggunakan metode bernyanyi untuk anak usia dini - Halizah, Nur (Maliki Interdisciplinary Journal, 2024)
One area where children must demonstrate independence is with regard to personal cleanliness. In early childhood education institutions, hand hygiene is a sort of personal hygiene that is socialized and practiced. The singing approach is one of the methods used in hand washing independence education. The purpose of this essay, according to the author, is to discuss the effectiveness of the singing technique as a teaching tool for independent hand hygiene practices. The singing method is helpful in helping kids remember the processes for properly washing their hands so they may practice it independently, according to the conclusion reached using a literature review.